2018
DOI: 10.1016/j.visres.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Tactile recognition of visual stimuli: Specificity versus generalization of perceptual learning

Abstract: Sensory substitution devices aim at assisting a deficient sensory modality by means of another sensory modality. For instance, to perceive with visual-to-tactile devices, users learn to recognize visual stimuli through their tactile conversion. A crucial characteristic of learning lies in the ability to generalize, that is, the ability to extend the acquired perceptual abilities to both new stimuli and new perceptual conditions. The study reported here investigated the perceptual learning of tactile alphanumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…6,8 Between these two extremes are the tactile and electrotactile SSDs. 5 Tactile SSD systems do provide a spatio-temporal stimulation that resembles that of vision but through sensory organs that may not convey visual perception. Evaluation of all these devices has relied primarily on MAFC testing, as commonly applied in clinical or psychophysical studies.…”
Section: Mafc Testing Of Prosthetic Vision Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8 Between these two extremes are the tactile and electrotactile SSDs. 5 Tactile SSD systems do provide a spatio-temporal stimulation that resembles that of vision but through sensory organs that may not convey visual perception. Evaluation of all these devices has relied primarily on MAFC testing, as commonly applied in clinical or psychophysical studies.…”
Section: Mafc Testing Of Prosthetic Vision Functionmentioning
confidence: 99%
“…It is not known if SSDs, such as tactile stimulation of the skin, 5 electrical stimulation of the tongue (for example, the BrainPort 4 ; Wicab, Inc.; Middleton, WI), or visual-to-auditory sensory substitution devices [6][7][8][9] lead to visual perception. All these SSD systems lead to a sensory response, but that is not necessarily vision as it is defined above.…”
Section: Introductionmentioning
confidence: 99%
“…This result provides behavioural support for the claim that training in sensory substitution results in a relative independence from the stimulated body surface. In addition, transfer of learning to novel stimuli has been documented for both tactile (Arnold and Auvray, 2018;Kim and Zatorre, 2010) and auditory devices (Kim and Zatorre, 2008). This ability to generalize to new symbols depends on the number of stimuli to learn and on feature variability (Arnold and Auvray, 2018).…”
Section: Sensory Substitution Learning and Body Kinematicsmentioning
confidence: 99%
“…In addition, transfer of learning to novel stimuli has been documented for both tactile (Arnold and Auvray, 2018;Kim and Zatorre, 2010) and auditory devices (Kim and Zatorre, 2008). This ability to generalize to new symbols depends on the number of stimuli to learn and on feature variability (Arnold and Auvray, 2018). These results are in line with the reverse hierarchy theory (RHT) of perceptual learning (Ahissar and Hochstein, 2004), according to which the degree of specificity depends on the difficulty of the perceptual task and on the level of cortical processing that is required to perform the task.…”
Section: Sensory Substitution Learning and Body Kinematicsmentioning
confidence: 99%
“…For example, Richardson et al (2020) used the Brain-Port to investigate the brain's construction of verticality through the tongue, showing it may be a viable tool to study other aspects of spatial construction. However, a possible issue with the BrainPort is that it maps the concept of "up" with the back of the tongue (see Figure 1), which may add a further spatial manipulation and may reduce user competence (Arnold et al, 2016;Arnold & Auvray, 2018;Pamir et al, 2020;Richardson et al, 2020). Further, recent work has suggested that the tongue suffers with an information "bottleneck" at the back, meaning that information presented to the front is a higher TACTILE ATTENTION ON THE SURFACE OF THE TONGUE 927 fidelity than that of the back (Pamir et al, 2020).…”
mentioning
confidence: 99%